2022
DOI: 10.1186/s13020-022-00651-2
|View full text |Cite
|
Sign up to set email alerts
|

Propolis: An update on its chemistry and pharmacological applications

Abstract: Propolis, a resinous substance produced by honeybees from various plant sources, has been used for thousands of years in traditional medicine for several purposes all over the world. The precise composition of propolis varies according to plant source, seasons harvesting, geography, type of bee flora, climate changes, and honeybee species at the site of collection. This apiary product has broad clinical applications such as antioxidant, anti-inflammatory, antimicrobial, anticancer, analgesic, antidepressant, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 431 publications
(485 reference statements)
0
64
0
Order By: Relevance
“…The Brazilian red propolis used by the authors was able to reduce gastric ulceration by 87.34% and 100.0% with doses of 250.0 and 500.0 mg/kg. The CHEBRP used in the present study was collected in Bahia, and its components differ from the Brazilian red propolis used by Mendonça et al [ 26 ] due to the geographical difference in propolis collection [ 22 ]. However, both the Brazilian red propolis, the one used in the present study and the one used by Mendonça et al [ 26 ] showed gastroprotective action in in vivo assays using Wistar rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Brazilian red propolis used by the authors was able to reduce gastric ulceration by 87.34% and 100.0% with doses of 250.0 and 500.0 mg/kg. The CHEBRP used in the present study was collected in Bahia, and its components differ from the Brazilian red propolis used by Mendonça et al [ 26 ] due to the geographical difference in propolis collection [ 22 ]. However, both the Brazilian red propolis, the one used in the present study and the one used by Mendonça et al [ 26 ] showed gastroprotective action in in vivo assays using Wistar rats.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids, phenolic compounds, esters, alcohols, terpenes and beta-steroids can be mentioned as important organic compounds already identified in propolis samples [ 21 ]. To date, the scientific literature has reported the identification of about 300 different chemical components in propolis from different sources [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its composition can be very different depending on the geographical area and botanical origin. Like honey, propolis is known to have antioxidant, antimicrobial, anti-inflammatory or even anti-carcinogenic effects [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Naringenin and dihydroxydecenoic acid were observed in all the samples, except for Aroeira and Coffee. Naringenin is a citrus flavonoid that has several biological activities such as sepsis, fulminant hepatitis, fibrosis and cancer [ 107 ]. Dihydroxydecenoic acid has an antineuroinflammatory effect and is the second most abundant fatty acid, but has been less studied in royal jelly, the results of these studies have revealed a new role for tumor suppressor p53 in the inhibition of neuroinflammation [ 108 ].…”
Section: Discussionmentioning
confidence: 99%